2008
DOI: 10.1002/masy.200851220
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Structure ‐ A Key Parameter for Cellulose Biodegradation

Abstract: Summary: Three different cellulosic substrata, like microcrystalline cellulose, cotton cellulose and spruce dissolving pulp, were chosen for biodegradation. The kinetics of the enzymatic hydrolysis of these celluloses by Trichoderma reesei, has been investigated. The experiments proved the fact that both the morphological structure and the crystalline one are crucial to the process and the ratio of the reactions. In addition, in order to obtain the most accessible cellulose substratum it was studied the biodeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
82
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 21 publications
8
82
0
1
Order By: Relevance
“…These peaks are normally identified for cellulose in commercial α-cellulose (Figure 2) [13,14]. The peak located at 1427.32 cm -1 which was observed in all specimens except untreated kenaf corresponds to the crystallinity band [15]. These results confirmed that the crystalline cellulose was successfully extracted from kenaf bast fibers in both treatments ( Table 1).…”
Section: Resultssupporting
confidence: 69%
“…These peaks are normally identified for cellulose in commercial α-cellulose (Figure 2) [13,14]. The peak located at 1427.32 cm -1 which was observed in all specimens except untreated kenaf corresponds to the crystallinity band [15]. These results confirmed that the crystalline cellulose was successfully extracted from kenaf bast fibers in both treatments ( Table 1).…”
Section: Resultssupporting
confidence: 69%
“…In contrast, the fine particles of the pulp-rich fraction are more brittle and consequently crumbly under the influence of applied frictions, owing to its low cellulose content. Indeed, according to Ciolacu et al [32], the crystallinity of the cellulose is at the origin of its resistance. The resulting fractions were compared to both the starting biomass (F0) and the reference fractions obtained by wet fractionation, in terms of color and biochemical composition in order to assess the efficiency of the applied dry fractionation routes.…”
Section: Dry Fractionationmentioning
confidence: 99%
“…Figure 1 shows that MCC scattering intensity of peaks decreases sharply after one hour milling. Onehour milling led to 30% reduction of the crystalline index measured according to equation (2). Hence, mechanical milling resulted in the increase of the amorphous regions number in MCC, but one hour of milling was not enough to transform MCC into amorphous cellulose, as there are some weak peaks on the XRD pattern.…”
Section: Resultsmentioning
confidence: 99%
“…Cellulose chains are located randomly in amorphous regions so interaction during reaction takes place more easily than in crystalline regions. Most of reactions takes place on plane of crystallites and in amorphous domains without affecting the intracrystalline regions [2]. The long-range order of crystalline in a mircofibril results from intermolecular interaction such as van der Waals's force and hydrogen bonds.…”
mentioning
confidence: 99%